Convergence of Biofabrication Technologies and Cell Therapies for Wound Healing - Motaharesadat Hosseini; Andrew J. Dalley; Abbas Shafiee (Pharmaceutics, 2022)
Background: Cell therapy holds great promise for cutaneous wound treatment but presents practical and clinical challenges, mainly related to the lack of a supportive and inductive microenvironment for cells after transplantation. Main: This review delineates the challenges and opportunities in cell therapies for acute and chronic wounds and highlights the contribution of biofabricated matrices to skin reconstruction. The complexity of the wound healing process necessitates the development of matrices with properties comparable to the extracellular matrix in the skin for their structure and composition. Over recent years, emerging biofabrication technologies have shown a capacity for creating complex matrices. In cell therapy, multifunctional material-based matrices have benefits in enhancing cell retention and survival, reducing healing time, and preventing infection and cell transplant rejection. Additionally, they can improve the efficacy of cell therapy, owing to their potential to modulate cell behaviors and regulate spatiotemporal patterns of wound healing. Conclusion: The ongoing development of biofabrication technologies promises to deliver material-based matrices that are rich in supportive, phenotype patterning cell niches and are robust enough to provide physical protection for the cells during implantation.